Strengthening Maternal Death Surveillance Systems for Evidence-Based Decision Making in Sub-Saharan Africa: The Case of the Center Region in Cameroon - Anastasia Bongajum Yenban; Pascal Foumane; Charlotte Moussi; Noel Vogue; Hycinth Banseka; Jujlius Nwobegahay; Martina Baye (Global Health and Education Projects, Inc., 2021)
Background: The article seeks to document the experience of implementing Maternal Death Surveillance and Response (MDSR) in the Center Region of Cameroon. The paper raises awareness on the need for implementing MDSR, shares progress and lessons learned and reflects on the implications for public health practice. Methods: A desk research involving the collection and analysis of secondary data using tables with specific themes in excel, following the review of existing resources at the Regional Delegation of Public Health-Center from the year 2016 to 2019. Results: The findings depict the existence of MDSR policies and sub-regional committees. Although, the number of regional maternal death notifications increased from 19 to 188 deaths between 2016 and 2019, the implementation of death review recommendations was only estimated at 10% in 2019. While 66% of deaths occurred in Yaoundé, 72% of these were deaths reported to have occurred in tertiary institutions out of which 75% were attributed to late referrals. Hemorrhage constituted 70/144 (48.6%) of the known direct causes of death. Maternal death related co-factors such as the use of partograph during labor had a high non-response rate (84%) and represents a weakness in the data set. Conclusion and Global Health Implications: Across the board, stakeholder engagement towards MDSR was increased through continuous awareness-raising, dissemination of surveillance tools, the institutionalization of the District Health Information Software (DHIS 2) and the "No Name No Blame" policy. However, the reporting and investigation of deaths for informed decisions remain a daunting challenge. For a resource-scarce setting with limited access to blood banks, the application of life-saving cost-effective interventions such as the use of partographs and the institution of a functional referral system among health units is likely to curb the occurrence of deaths from hemorrhage and other underlying causes. The success of these will require a robust strengthening of the health system.   Copyright © 2021 Bongajum, et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0.